A structured, telephone-delivered intervention to reduce methamphetamine use: study protocol for a parallel-group randomised controlled trial - Dan I. Lubman; Victoria Manning; Shalini Arunogiri; Kate Hall; John Reynolds; Peta Stragalinos; Rachel Petukhova; Robyn Gerhard; Jonathan Tyler; Anna Bough; Anthony Harris; Jasmin Grigg (Trials, 2023)
Abstract Background Australia has one of the highest rates of methamphetamine (MA) use in the world; however, uptake of in-person psychological treatment remains extremely low due to numerous individual (e.g. stigma, shame) and structural (e.g. service accessibility, geographical location) barriers to accessing care. Telephone-delivered interventions are ideally placed to overcome many of the known barriers to treatment access and delivery. This randomised controlled trial (RCT) will examine the efficacy of a standalone, structured telephone-delivered intervention to reduce MA problem severity and related harms. Methods This study is a double-blind, parallel-group RCT. We will recruit 196 ± 8 individuals with mild to moderate MA use disorder from across Australia. After eligibility and baseline assessments, participants will be randomly allocated to receive either the Ready2Change-Methamphetamine (R2C-M) intervention (n = 98 ± 4; four to six telephone-delivered intervention sessions, R2C-M workbooks and MA information booklet) or control (n = 98 ± 4; four to six ≤5-min telephone check-ins and MA information booklet including information on accessing further support). Telephone follow-up assessments will occur at 6 weeks and 3, 6 and 12 months post-randomisation. The primary outcome is change in MA problem severity (Drug Use Disorders Identification Test, DUDIT) at 3 months post-randomisation. Secondary outcomes are as follows: MA problem severity (DUDIT) at 6 and 12 months post-randomisation, amount of methamphetamine used, methamphetamine use days, methamphetamine use disorder criteria met, cravings, psychological functioning, psychotic-like experiences, quality of life and other drug use days (at some or all timepoints of 6 weeks and 3, 6 and 12 months post-randomisation). Mixed-methods program evaluation will be performed and cost-effectiveness will be examined. Discussion This study will be the first RCT internationally to assess the efficacy of a telephone-delivered intervention for MA use disorder and related harms. The proposed intervention is expected to provide an effective, low-cost, scalable treatment for individuals otherwise unlikely to seek care, preventing future harms and reducing health service and community costs. Trial registration ClinicalTrials.gov NCT04713124 . Pre-registered on 19 January 2021.